2013
DOI: 10.1002/cbf.2967
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of N‐acetylcysteine against ischemia/reperfusion injury in rat urinary bladders

Abstract: Ischemia/reperfusion (I/R) injury represents an important cause of bladder contractile dysfunction. One of the major causes leading to this dysfunction is thought to be reactive oxygen species formation. In this study, we investigated the potential benefit of N-acetylcysteine (NAC), a potent antioxidant that neutralizes free radicals, in a rat model of urinary bladder injury. NAC treatment rescues the reduction of contractile response to I/R injury in a dose-dependent manner. In addition, all levels of reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Overactive bladder (OAB) is prevalent in patients or animal models with diabetes [ 12 ], bladder outlet obstruction [ 13 ], chronic ischemia [ 14 ], ischemia/reperfusion [ 15 ], or ageing [ 16 ]. These pathophysiological conditions are also characterized by excessive accumulation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Overactive bladder (OAB) is prevalent in patients or animal models with diabetes [ 12 ], bladder outlet obstruction [ 13 ], chronic ischemia [ 14 ], ischemia/reperfusion [ 15 ], or ageing [ 16 ]. These pathophysiological conditions are also characterized by excessive accumulation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we showed that bladder I/R injury leads to the formation of lipid peroxidation [ 14 ]. Considering these results, the above finding, which indicated that allopurinol had antioxidant effects, prompted us to determine whether allopurinol treatments can also regulate the levels of lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…MDA amounts were assayed with a thiobarbituric acid reactive substances (TBARS) kit (ZeptoMetrix), which is based on a spectroscopic method. MDA levels were performed according to standard protocol as previously described [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several other agents possessing such properties have been shown to have protective effects against ischemia-reperfusion bladder injuries, for example, co-enzyme Q [Juan et al 2008; Kim et al 2013], N-acetylcysteine [Shin et al 2014], eviprostat [Matsui et al 2012; Kawai et al 2013] and edaravone [Matsumoto et al 2010]. Some of these agents may also be useful for protection against the effects of chronic bladder ischemia.…”
Section: Free Radical Scavengingmentioning
confidence: 99%